2020
DOI: 10.1017/dmp.2019.154
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life After the 2015 Gorkha Earthquakes, Among Older Adults Living in Lalitpur District of Central Nepal

Abstract: Objective: Health-related quality of life (HQL) among older adults is often neglected and underprioritized in developing countries and is further burdened during natural disasters, such as earthquakes. The main objective of this study was to explore the factors affecting HQL among older adults living in Lalitpur District of Nepal. Methods: A total of 362 older adults participated in this study. Questionnaires were used to interview the respondents on various aspects, such as posttraumati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Studies among the elderly from Korea and Bangladesh also reported associations between depression and lower QOL [64,65]. The only study from Nepal assessing QOL after major trauma was also among the elderly from a city area, where higher age and PTSD diagnosis were associated with poorer QOL even 1.5 years after the trauma [66]. Another study from Nepal on old-age home residents also reported associations between depression and all four QOL domains [67].…”
Section: Discussionmentioning
confidence: 98%
“…Studies among the elderly from Korea and Bangladesh also reported associations between depression and lower QOL [64,65]. The only study from Nepal assessing QOL after major trauma was also among the elderly from a city area, where higher age and PTSD diagnosis were associated with poorer QOL even 1.5 years after the trauma [66]. Another study from Nepal on old-age home residents also reported associations between depression and all four QOL domains [67].…”
Section: Discussionmentioning
confidence: 98%
“…16 A recent study from Nepal echoes our findings and shows that the older adults were vulnerable to have a poorer health-related quality of life. 12 The older population was found to be the most affected group during the earthquakes in Japan, China, Haiti, India, and California. 8,10,16,17 Although various factors play a synergistic role for the cumulative impact, 18 the older adults in Nepal were further made vulnerable due to their homebound nature, low mobility (due to disability and debility as a result of old age), and comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,16,17 Although various factors play a synergistic role for the cumulative impact, 18 the older adults in Nepal were further made vulnerable due to their homebound nature, low mobility (due to disability and debility as a result of old age), and comorbid conditions. 9,12 In general, delayed response is observed among the elderly population who often suffer from comorbid conditions, including depression. 19 More than half (57% of 289 patients) of the elderly population attending general Out-Patient Department in Kathmandu were found to be suffering from depression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations